Combined effects of material properties and boundary conditions on the large deflection bending analysis of circular plates on a nonlinear elastic foundation - Altekin, Murat (TECHNO-PRESS, 2020)
Geometrically nonlinear axisymmetric bending analysis of shear deformable circular plates on a nonlinear three-parameter elastic foundation was made. Plates ranging from thin to moderately thick were investigated for three types of material: isotropic, transversely isotropic, and orthotropic. The differential equations were discretized by means of the finite difference method (FDM) and the differential quadrature method (DQM). The Newton-Raphson method was applied to find the solution. A parametric investigation using seven unknowns per node was presented. The novelty of the paper is that detailed numerical simulations were made to highlight the combined effects of the material properties and the boundary conditions on (i) the deflection, (ii) the stress resultants, and (iii) the external load. The formulation was verified through comparison studies. It was observed that the results are highly influenced from the boundary conditions, and from the material properties.
Keywords: plate; nonlinear; Pasternak; Winkler; foundation; deflection; FREE-VIBRATION ANALYSIS; FUNCTIONALLY GRADED PLATE; DYNAMIC-RESPONSE; ANNULAR PLATES; COMPOSITE PLATES; LAMINATED PLATES; DAMAGE DETECTION; ELLIPTIC PLATES; FORMULATION; Computer Science; Construction & Building Technology; Engineering; Materials Science